Knowledge Sharing Behavior, Team Climate, and Organizational Learning Culture as Predictors of Innovative Work Behavior - Ika Nurfitriani Listyanti; Achmad Fajar Hendarman (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2023)
Innovative work behavior has become an important research topic in human resource management. In the current fast-paced environment, organizations have also been forced to rely more on people to innovate to stay ahead of the competition. Addressing both the theoretical and practical purposes, this study investigated the roles of knowledge sharing behavior, team climate, and organizational learning culture in predicting innovative work behavior. A self-report questionnaire was used to collect data from employees in a telecommunication company in Indonesia with a total of 155 responses. Regression analysis revealed that knowledge sharing behavior, team climate, and organizational learning culture predicted employees’ innovative work behavior, which was consistent with previous findings. These results contribute to the existing literature by providing evidence that individual, group, and organizational factors should always be considered when predicting innovative work behavior.